A Case of Stevens–Johnson Syndrome Complicated with Multimatrix System Mesalamine in Ulcerative Colitis - Mimari Kanazawa; Keiichi Tominaga; Akira Kanamori; Takanao Tanaka; Satoshi Masuyama; Shoko Watanabe; Keiichiro Abe; Akira Yamamiya; Kenichi Goda; Atsushi Irisawa (Medicina, 2022)
A 41-year-old man was treated with prednisolone (PSL) and multimatrix (MMX) mesalamine for remission induction therapy of ulcerative colitis. PSL was tapered due to successful remission induction treatment. During the treatment course, ocular foreign body sensation, eyelid swelling, ocular conjunctiva hyperemia, facial redness and swelling, watery nasal discharge, stomatitis, anal pain, and reddish puffiness on the bilateral dorsum of the hands appeared, and he was diagnosed with Stevens–Johnson syndrome (SJS). SJS was improved by PSL treatment and intravenous immunoglobulin. MMX mesalamine was the causative agent by drug-induced lymphocyte stimulation test. This is the first reported case of SJS with MMX mesalamine.